Magnetoresistance of Fe3O4-graphene-Fe3O4 junctions - DUESBERG, GEORG; WU, HAN-CHUN; WANG, JING; CROSS, GRAHAM; KUMAR, SHISHIR; SHVETS, IGOR (My University, 2011)
The magnetoresistance (MR) of Fe3O4-graphene-Fe3O4 junctions has been experimentally studied at different temperatures. It is found that a barrier exists at the Fe3O4/graphene interface. The existence of the interfacial barrier was further confirmed by the nonlinear I-V characteristics and nonmetallic temperature dependence of the interfacial resistance. Moreover, spin dependent transport at the interfaces contributes ?1.6% MR to the whole device at room temperature and can be regulated by an external electric field.
PUBLISHED
Keywords: Atomic, molecular and chemical physics; graphene; Nanoscience & Materials